Memories of Public Libraries in Oral Histories of Accomplished Black Professionals: Methods of Finding the Library in the Life of the User. - Knowlton, Steven A. (Information & Culture, 2025)
I mined 503 oral histories of prominent Black Americans for their memories of public libraries in the twentieth-century United States. I then analyzed testimonies to produce a "prosopography of sentiment": aggregated data demonstrating how members of this demographic group in general felt about libraries. The most common themes were "reading as a pleasurable activity," "library as a source to explore Black culture or develop Black pride," and "library as a site for personal growth or maturation." The most common theme with unpleasant emotional valence was "stories related to segregation or discrimination." Most memories occurred during reporters' childhoods or adolescences. The percentage of stories with unpleasant emotional valence declines significantly from the 1920s to the 1970s and as the population of the city increases. Within this demographic group, memories of the library often confirm the stereotypes that library advocates tend to promote.